To pay, or not to pay: whether ’tis tastier To indulge in cookies Or guard thy privacy - Fredholm, Viktor; Hansson, Simon (My University, 2023)
The experience of browsing the web and lazily clicking cookie consent go hand in hand for many. However, it has been shown that the majority of these cookie banners do not adhere to the GDPR and ePrivacy Directive. Based on previous findings that there is a new type of cookie banner, cookie paywalls, where denial of consent is replaced by a fee. Our study presents results showing how well cookie paywalls comply with the GDPR. Our results show that the majority of websites implementing cookie paywalls do not contain any major violations of the GDPR and ePD. However, many different implementations exist. Some contain dark patterns, and some misuse legitimate interest. With websites using dark patterns, it is feasible to question if there is any actual interest in being paid.
Keywords: Computer; science; engineering; project; thesis; cookies; cookie paywall; paywalls; legitimate interest